Peranan Biogas Limbah Ternak Sapi Bantuan PT. Petrochina Bagi Peternak Di Kabupaten Tanjung Jabung Timur Provinsi Jambi - Darmawi, Darlim (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The research is aimed to find out how much is the production of biogas from cow dirt, subsidized by PT Petrochina, and it’s role to fulfill veterinarian’s necessity at Tanjung Jabung Timur regency. The research’s  method  is  survey  method  by  using  analysis  unit  of  cow  veterinarians  subsidized  by  PT Petrochina. The research’s respondents are choosen purposively (Nasir M 1983). The analysis used here is  descriptive  analysis.  The  analysis  result  shows  that  from  33  people  (100%  of  respondents),  the total amount of veterinarian has got cow as much as 65,5 UT and could get cow’s dirt as much as 8952,72 kg / KK /  year and resulted biogas in average  as much as 1253,39 M 3 /KK/year.  While, before  veterinarian used biogas, they have spent gasoline and wood as much as 273,72 litre/KK / year and 303,88 bounded of wood  /  KK/year.  In  conclusion,  biogas  has  important  role  as  alternative  energy  for  veterinarian  to sustitute gasoline and  woods, and could ease energy  cost so that veterinarian need only 1.177.125 litre gasoline/ KK / year and 1.311.237 bounded of wood / KK / year.